Geological occurrence and productivity prediction for coalbed methane of central Hunan depression, China - Cai, Ningbo; Wang, Keying; Du, Jiang (Frontiers in Earth Science, 2022)
To analyze the geological occurrence and predict the drainage performance of coalbed methane in central Hunan depression of China, coal samples were collected to conduct physical experiments and numerical simulations. Following conclusions are achieved. The vitrinite ranges from 54.37 % to 87.80 %, the inertinite is between 11.14-25.89 %, and exinite is less than 1 %. The inorganic components are mainly clay minerals and vary from 0.71 % to 5.66 %. The major porosity ranges from 7 % to 9 %, and it is influenced by organic/ inorganic components and maturity. Both the vertical and horizontal permeabilities are at a relatively low level, mostly below 0.05 mD, indicating the reservoir is low permeable or non-permeable. The reservoir pressure ranges from 3.74 MPa to 11.58 MPa, which has significantly and positively linear correlations with closure pressure and burial depth. Gas content varies from 5 m3/t to 20 m3/t. The theoretical recovery ratio in the Hongshandian mining area is about 61.7 %, while the values of the two spots in the Duanpiqiao mining area are 49.1 % and 54.5 %. Production predictions show that under the permeability of 0.01 mD, 0.05 mD, and 0.10 mD, cumulative gas productions in ten years for a single well range from 1.7×106 m3 to 3.2×106 m3, and those for a well group consisting of five wells vary from 10.5×106 m3 to 19.2×106 m3. Thus, this area will have a high value for coalbed methane exploitation after stimulating the reservoir to increase permeability successfully.